Modelling Interest- Free Economy, A Study in Macro-Economics and Development (American Journal of Islam and Society, 1989)
In recent years there has been numerous Islamic publications in bothsocial and economic fields trying to establish their theoretical and empiricalbasis according to Islamic principles Modelling Interest-Free Economy, AStudy in Macro-economics and Development by Dr. Muhammad Anwar isone book which is a laudable study in economics, applying particularly themudaraba system to the macro-economic level. Although it is really valuablestudy, I would like to express my opinions on the following points.1) Regarding the technical points, it would have been useful for the readerif the sources used as reference had been given as footnotes. It is difficultto refer back to the sources.2) “Muslim countries are reforming their financial systems in the light ofIslamic teachings. Islamic financial institutions conduct their operationsin ways that steer clear of interest and conform to the Sharia, the Islamiccode of law and ethics (p. 7).” In such studies, it would be useful todraw a clear line between trade activities and partnerships and thebanking system. Since Islamic countries and Muslim scholars are justnow trying to develop a new banking system according to Islamic principles,we should be strictly careful when using the term “Islamic Banks.”In contrast with some Muslim scholars, for similar reasons we shouldalso be careful when putting forward the mudaraba system as the basisfor a banking or economic system. Instead of calling these institutions“Islamic” it would be more proper to use such terms as “Interest-FreeCommercial Institutions”, “Interest-Free Financial Institutions”, “Interest-Free Credit Institutions (Corporations) ,” etc.3) The mudaraba contract as a form of partnership is directly related totrading activities. The involvement of the banking system in trade activitiesby establishing partnerships with certain firms through mudarabacontracts can severely distort the free competition in the market systemwhich is encouraged by the Prophet (SAAS). Banks are institutions inwhich huge amounts of financial resources are accumulated. As the banksenter the market to make commercial transactions, even though in theforms of mudaraba, musharaka or murabaha, this involvement will likely ...